WORK-LIFE BALANCE - CHALLENGES OF GENDER EQUALITY IN THE LABOR MARKET IN THE REPUBLIC OF NORTH MACEDONIA VS EUROPEAN UNION (EU and comparative law issues and challenges series (ECLIC), 2020)
Work-life balance is the term used to describe practices in achieving a balance between the demands of employees’ family (life) and work lifes. Employers today strive to augment job satisfaction in the workforce for it is conducive to lower employee turnover, higher engagement, and greater productivity. Besides the feminists, who discuss women’s inequality with men in the family and the separation of the family responsibilities, the term “work-life balance”, addressing the aspects of achieving this balance, starts to be more commonly used in employment policies. The dramatic increase in female labor force participation in the labor market, as a result of the collapse of the so-called “male breadwinner” model, often results in a “double burden” for paid women. On the other hand, there is a tendency among employers to increase workforce satisfaction because it has been shown to reduce employee turnover and produce higher engagement and increased productivity. Policies for the harmonization of work and private life are covered by social legislation and labor legislation. The International Labor Organization defines the work-life balance as one of the greatest challenges of our time. One of the aims of the European Social Rights Pillar is the Work-life balance Initiative which addresses the challenges of work-family balance faced by working parents and carers. Therefore, a directive on the balance between the working and professional life of parents and carers have recently been adopted in the European Union. It sets several new or higher standards for absent parents, paternity and guardianship and enforces a greater use of flexible employment contracts. Its aim is to increase the inclusion of women in the labor market and to promote greater use of parental leave by male workers. Motivated by this, a comparative analysis and critical overview is made between the policies existing in the member states of the European Union and the Republic of North Macedonia which are directly related to the promotion of family-work balance. The purpose of this paper is to see how the Macedonian labor and the legal system is prepared to respond to the challenge posed by this Directive and to provide suggestions and guidance that would improve the situation in the domestic labor market.